2018
DOI: 10.1186/s12991-018-0187-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between parental depression and adolescent’s Internet addiction in South Korea

Abstract: BackgroundA number of risk factors for Internet addiction among adolescents have been identified to be associated with their behavior, familial, and parental factors. However, few studies have focused on the relationship between parental mental health and Internet addiction among adolescents. Therefore, we investigated the association between parental mental health and children’s Internet addiction by controlling for several risk factors.MethodsThis study used panel data collected by the Korea Welfare Panel St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 27 publications
4
27
1
Order By: Relevance
“…However, a very recent study revealed problematic phone use was positively associated with time spent with children during meals, but it was significantly and positively associated with technology interference in 9 of 11 parenting domains (e.g., playtime, mealtime, and playtime excursions) and maternal depression was associated with problematic phone usage, which in turn was associated with technology interference in parenting [ 34 ]. Lastly, we found children's internet addiction is associated with the mother's depression as a recent South Korean study aligns with our findings [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, a very recent study revealed problematic phone use was positively associated with time spent with children during meals, but it was significantly and positively associated with technology interference in 9 of 11 parenting domains (e.g., playtime, mealtime, and playtime excursions) and maternal depression was associated with problematic phone usage, which in turn was associated with technology interference in parenting [ 34 ]. Lastly, we found children's internet addiction is associated with the mother's depression as a recent South Korean study aligns with our findings [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…spent with children during meals, but it was significantly and positively associated with technology interference in 9 of 11 parenting domains (e.g., playtime, mealtime, and playtime excursions) and maternal depression was associated with problematic phone usage, which in turn was associated with technology interference in parenting [34]. Lastly, we found children's internet addiction is associated with the mother's depression as a recent South Korean study aligns with our findings [35]. Due to study design, the opposite direction of association needs to be considered as mothers with depression have poorer quality interactions, are less emotionally available, and can negatively report their children's behavior [36,37,38].…”
Section: Discussionsupporting
confidence: 89%
“…Parental depression has been related to children's IGD in a population sample in Hong Kong (Lam, 2015), and has been associated with negative impacts relating to IGD in Korean adolescents (Choi et al, 2018). However, these findings were derived from cross-sectional surveys in which temporal relationships could not be determined between parental depression and IGD in children (Lam, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…There are several empirical evidences on the problematic behavior in children and adolescents that have been associated with mental health problems in their parents (Burleigh, Stavropoulos, Liew, Adams, & Griffiths, 2018;Erceg et al, 2018;Loechner et al, 2020;Paquin et al, 2020). Especially parental depression plays a significant role in the development of IGD among children and adolescents (Choi, Chun, Lee, Han, & Park, 2018;Lam, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Addictive tendencies of Internet use have been empirically investigated in a variety of contexts. Various samples have been studied, including medical students (Zhang, Lim, Lee, & Ho, 2017), college students in China (Shao et al, 2018), and adolescents in South Korea (Choi, Chun, Lee, Han, & Park, 2018). Past research indicated that as tendencies of shyness increase, addictive tendencies of Internet use increase to reduce feelings of loneliness (Ang, Chan, & Lee, 2017).…”
Section: Internet Usementioning
confidence: 99%